Spread of the arrow bulleye Priacanthus sagittarius Starnes, 1988 in the Mediterranean Sea - Gökoğlu, Mehmet; Teker, Serkan (Universitas Malikussaleh, 2018)
Habitat of the family Priacanthidae is tropical and subtropical Atlantic, Indian, and Pacific oceans. The features of the family members are generally very big eyes, deep bodies, upturned mouth, and generally reddish color. In the this paper, we report the presence of an arrow bulleye Priancanthus sagittarius in coast of Turkey waters in the Mediterranean Sea. On the 27th December, 2017, a single specimen of P. sagittarius was collected by Mr. Hüseyin Ã‡Ä±nar, captain of the commercial bottom trawler Furkan Reis vessel, off the TaÅŸucu, Mersin (36°07'2.82